Mitochondrial Fusion Protein Mfn2 and Its Role in Heart Failure - Chen, Lei; Liu, Bilin; Qin, Yuan; Li, Anqi; Gao, Meng; Liu, Hanyu; Gong, Guohua (Frontiers in Molecular Biosciences, 2021)
Mitofusin 2 (Mfn2) is a transmembrane GTPase located on mitochondrial outer membrane that contributes to mitochondrial network regulation. It is an essential multifunctional protein that participates in various biological processes under physical and pathological conditions, including mitochondrial fusion, reticulum-mitochondria contacts, mitochondrial quality control, and apoptosis. Mfn2 dysfunctions have been found to contribute to cardiovascular diseases, such as ischemia-reperfusion injury, heart failure, dilated cardiomyopathy. Here, this review mainly focuses on what is known about the structure and function of Mfn2 and its crucial role in heart failure.